2006
DOI: 10.1109/tmc.2006.174
|View full text |Cite
|
Sign up to set email alerts
|

A Theory of Network Localization

Abstract: In this paper we provide a theoretical foundation for the problem of network localization in which some nodes know their locations and other nodes determine their locations by measuring the distances to their neighbors. We construct grounded graphs to model network localization and apply graph rigidity theory to test the conditions for unique localizability and to construct uniquely localizable networks.We further study the computational complexity of network localization and investigate a subclass of grounded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
408
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 563 publications
(409 citation statements)
references
References 64 publications
1
408
0
Order By: Relevance
“…In molecular conformation (see, e.g., [9,26]), solving the GRP in dimension three allows construction of the 3-dimensional structure of the molecule. In wireless sensor network localization (see, e.g., [6,16]), where one is interested in inferring the locations of sensor nodes in a sensor network. And in computer vision, where image reconstruction is performed from selected pairwise distances of labeled sources [8,25].…”
Section: Introductionmentioning
confidence: 99%
“…In molecular conformation (see, e.g., [9,26]), solving the GRP in dimension three allows construction of the 3-dimensional structure of the molecule. In wireless sensor network localization (see, e.g., [6,16]), where one is interested in inferring the locations of sensor nodes in a sensor network. And in computer vision, where image reconstruction is performed from selected pairwise distances of labeled sources [8,25].…”
Section: Introductionmentioning
confidence: 99%
“…A graph is a trilateration extension if it has a trilateration ordering. It is shown that trilateration extensions are globally rigid [69,76] .…”
Section: Trilaterationmentioning
confidence: 99%
“…Since our graph matching cannot localize sensors correctly, due to the topology symmetricity, we need anchor nodes that are sensors with GPS receivers. We need to determine whether we can localize sensors uniquely by testing the conditions for unique localizability discussed in [1]. If there is a topology symmetricity in the road network, we need to find out a minimum number of anchor nodes and the places to remove the ambiguity for graph matching before applying our localization scheme to the road network.…”
Section: Matching Ambiguity Due To Topology Symmetricitymentioning
confidence: 99%